Connecting Cape Breton Island and Newfoundland, Canada: Geophysical Modeling of pre-Carboniferous ‘Basement’ Rocks in the Cabot Strait Area - Barr, Sandra; Dehler, Sonya; Zsámboki, Louis (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2014)
Magnetic and gravity data from northeastern Cape Breton Island, southwestern Newfoundland, and the intervening Cabot Strait area were compiled and used to generate a series of maps displaying magnetic (filtered total field, first and second derivative) and gravity (Bouguer anomaly onshore, free-air anomaly offshore) information to enhance the anomaly pattern associated with regional geology. With further constraints from previously published seismic reflection interpretations and detailed maps of onshore geology, five two-dimensional subsurface models were generated. Potential field anomalies in the offshore can be correlated with onshore faults, rock units, and pre-Carboniferous terranes. In Newfoundland, the Cabot – Long Range Fault separates Grenvillian basement to the northwest from peri-Gondwanan Port aux Basques subzone basement in the southeast and can be traced to the Wilkie Brook Fault on Cape Breton Island. The Cape Ray Fault/Red Indian Line merges offshore with the Cabot – Long Range Fault so that Notre Dame subzone rocks do not extend across the Cabot Strait area. The Port aux Basques – Exploits subzone boundary crosses the strait but is likely buried by younger rocks onshore in Cape Breton Island. Magnetic halos in the Exploits subzone are probably caused by Silurian – Devonian plutons like those in the Burgeo Intrusive Suite. The Exploits – Bras d’Or terrane boundary is located within the Ingonish magnetic anomaly, which was resolved into four overlapping components representing basement sources intruded into metasedimentary rocks and dioritic and granodioritic plutons of the Bras d’Or terrane. The Bras d’Or terrane can be traced to the Cinq-Cerf block and Grey River areas in southern Newfoundland. The interpretations suggest that Bras d’Or terrane ‘basement’ may underlie all of Exploits subzone, and that the Aspy terrane of Cape Breton Island is part of that subzone.